2020
DOI: 10.1002/cam4.2960
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen is a candidate first‐in‐class inhibitor of acid ceramidase that reduces amitotic division in polyploid giant cancer cells—Unrecognized players in tumorigenesis

Abstract: Polyploid giant cancer cells (PGCC) represent a poorly understood, small subpopulation of tumor cells that are increasingly being recognized for their critical role in therapy resistance, metastasis, and cancer recurrence. PGCC have the potential to generate progeny through primitive or cleavage-like division, which allows them to evade antimitotic insults. We recently demonstrated that the sphingolipid enzyme acid ceramidase (ASAH1) is required for this process. Since specific ASAH1 inhibitors are not clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…Growth of GBM cells in vitro can be inhibited by acid CDase inhibitors such as carmofur [ 77 , 169 ]. Additionally, tamoxifen, a treatment for ER-positive breast cancer, has been shown to inhibit acid CDase and readily crosses the BBB [ 170 ]. As an already approved therapy, this provides potential application for the treatment of GBM.…”
Section: Altering Sphingolipid Metabolism For Therapeutic Intervenmentioning
confidence: 99%
“…Growth of GBM cells in vitro can be inhibited by acid CDase inhibitors such as carmofur [ 77 , 169 ]. Additionally, tamoxifen, a treatment for ER-positive breast cancer, has been shown to inhibit acid CDase and readily crosses the BBB [ 170 ]. As an already approved therapy, this provides potential application for the treatment of GBM.…”
Section: Altering Sphingolipid Metabolism For Therapeutic Intervenmentioning
confidence: 99%
“…Polyploid giant cancer cells (PGCCs) are ubiquitous in human cancerous tissues, which contain enlarged or multiple nuclei with increased genomic content when compared to other cancer cells in the same tumor [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that ASAH1 expression increases in PGCC and its activity is critical for PGCC progeny formation across cell lines from different types of cancer [ 13 , 14 ]. To better understand the specific dependence of PGCC on ASAH1, LC/MS analysis was performed to analyze sphingolipid profiles in parental PPC1 cells and their PGCC derivatives in the presence and absence of the ASAH1 inhibitor LCL521.…”
Section: Resultsmentioning
confidence: 99%
“…We recently identified the sphingolipid enzyme acid ceramidase (ASAH1) as the first molecular target for interfering with the generation of progeny from PGCC [ 13 ]. ASAH1 resides in the lysosome, where it hydrolyzes ceramides to generate sphingosine, which serves as a substrate for sphingosine kinase 1 or 2 (SphK1 and SphK2) that through the addition of a phosphate group generate sphingosine-1-phosphate (S1P) [ 13 , 14 ]. Ceramides and S1P are functionally opposed, with the former generally considered pro-apoptotic and the latter playing roles in survival, mitosis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%